Characterization of Stanniocalcin-1 Receptors in the Rainbow Trout. (6th February 2012) - Richards, Timothy D. J.; Fenton, Amanda L.; Syed, Rahma; Wagner, Graham F.
Abstract : Mammalian stanniocalcin-1 (STC-1) is one of several ligands targeted to mitochondria. High affinity STC-1 receptors are present on the mitochondrial membranes of nephron cells, myocytes, and hepatocytes, to enable ligand sequestration within the matrix. However, STC-1 receptors have not been characterized in fish. Nor is it known if mitochondrial targeting occurs in fish. The aim of the study was to address these questions. Saturation binding assays were carried out to obtain estimates of K D and B max . They revealed the presence of saturable, high-affinity receptors on both membranes and mitochondria of liver, muscle, and gill filament. In situ ligand binding (ISLB) was used to localize receptors at the histological level and revealed some unexpected findings. In cranium, for instance, receptors were found mainly in the cartilage matrix, as opposed to the chondrocytes. In brain, the majority of receptors were located on neuropil areas as opposed to neuronal cell bodies. In skeletal muscle, receptors were confined to periodic striations, tentatively identified as the Z lines. Receptors were even found on STC-1 producing corpuscles of Stannius cells, raising the possibility of there being an autocrine feedback loop or, perhaps, a soluble binding protein that is released with the ligand to regulate its bioavailability.